Reversible addition-fragmentation chain transfer copolymerization of styrene/divinylbenzene in aqueous suspension - Gonçalves, Miguel A.D. (2012)
The Reversible Addition-Fragmentation Chain Transfer (RAFT) copolymerization of styrene (S) and divinylbenzene (DVB) was performed at temperature range 110 to 150 °C in aqueous suspension, using AIBN as thermal initiator and 2-dodecylthiocarbonothioylthio-2-methylpropionic acid (DDMAT) as RAFT agent.